2019
DOI: 10.1590/1806-3713/e20170164
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin effects on pulmonary tissue in the experimental model of Hepatopulmonary Syndrome

Abstract: Objective: To evaluate the pulmonary alterations of animals with Hepatopulmonary Syndrome (HPS) submitted to Biliary Duct Ligature (BDL), as well as the antioxidant effect of Melatonin (MEL). Methods: Sixteen male Wistar rats, divided into four Sham groups: BDL group, Sham + MEL group and BDL + MEL. The pulmonary and hepatic histology, lipoperoxidation and antioxidant activity of lung tissue, alveolar-arterial O2 difference and lung / body weight ratio (%) were evaluated. Results: When comparing the groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Most articles included in this systematic review have reported the antioxidant and anti‐inflammatory actions of melatonin as part of its antifibrotic effects. Similarly, several investigations carried out with different hepatic disease models have also reported antioxidant properties of melatonin directly related to its positive activity on abrogating NAFLD and hepatic ischemic injury, among others (Bosco et al, 2019; Joshi et al, 2021; H. W. Li et al, 2021). Together with oxidative stress, inflammation is a process highly associated with hepatic damage (Mortezaee & Khanlarkhani, 2018), where melatonin has also been demonstrated to modulate the inflammatory response in several liver pathologies by restraining an overactivated response derived from chronic liver injury (Laliena et al, 2012; H. W. Li et al, 2021) or even from hepatotoxicity (Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…Most articles included in this systematic review have reported the antioxidant and anti‐inflammatory actions of melatonin as part of its antifibrotic effects. Similarly, several investigations carried out with different hepatic disease models have also reported antioxidant properties of melatonin directly related to its positive activity on abrogating NAFLD and hepatic ischemic injury, among others (Bosco et al, 2019; Joshi et al, 2021; H. W. Li et al, 2021). Together with oxidative stress, inflammation is a process highly associated with hepatic damage (Mortezaee & Khanlarkhani, 2018), where melatonin has also been demonstrated to modulate the inflammatory response in several liver pathologies by restraining an overactivated response derived from chronic liver injury (Laliena et al, 2012; H. W. Li et al, 2021) or even from hepatotoxicity (Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…By removing free radicals, melatonin may adequately modulate autophagy pathways and apoptosis, which are key mechanism in the development of idiopathic pulmonary fibrosis [58]. Additionally, the utilization of melatonin in the treatment of animals with induced hepatopulmonary syndrome was effective in the reduction of lung fibrosis levels, vasodilation, and oxidative stress [59].…”
Section: Melatonin and Its Effects On Inflammation And Oxidation At Lung Levelmentioning
confidence: 99%
“…Melatonin has been hypothesized to remove free radicals, and therefore may modulate autophagy pathways and apoptosis, which are critical factors in the development of idiopathic pulmonary fibrosis ( 10 ). In addition, the use of melatonin in animals (rats and rabbits), with induced hepatopulmonary syndrome, has been proven to be beneficial in the reduction of lung fibrosis levels, oxidative stress and vasodilation ( 45 ).…”
Section: Suggested Mechanisms Of Action Of Melatonin Against Viralmentioning
confidence: 99%